National Agricultural Market (e-NAM) - A Case of its Implementation in Rajasthan - K, Shalendra; Jairath, MS; Gummagolmath, KC (Journal of Agricultural Extension Management, 2018)
The concept of National Agricultural Market has made an impressive progress since its launch on 14th April 2016. A total of 585 markets from 18 states/UTs so far have been integrated with the common platform. In this paper an attempt has been made to assess the performance of the concept at the national and state level. The performance at national level has been evaluated using secondary information on the number of markets integrated, volume of trade and registration of stakeholders on the portal. An attempt has also been made to assess the impact of the initiative on aspects like price discovery though with special focus on the state of Rajasthan. The analysis at the national level suggests encouraging balanced spread of states as nearly two-third of the markets are participating in the Scheme from just five states. There is a need for creation of awareness among farmers and other stakeholders to help them understand the benefits and procedure of eNAM. They are also required to be trained on preparing the produce as per the requirements of such a market. In order to reap benefits of the initiative, it is required to adopt different means like capacity building of stakeholders and creation of requisite support infrastructure to improve trade on the e-portal. A commodity-focused approach in place of a wide range of commodities may yield better result. The concept has the potential to provide a solution to various problems prevailing in agricultural marketing as has been suggested by the response of the stakeholders and positive influence of the initiative on scientific price discovery.